Azuki bean: botany, production and uses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Azuki bean is one of the twelve most important grain legumes in the world and is grown widely in China, Japan, South Korea and Taiwan. It has also been produced or studied in several other countries, including the USA, Argentina and Australia....